The Interpretive Study of the Root "H F Z" (ح ف ظ) in the Ninth Verse of Surah Al-Hijr, with an Emphasis on the Semantic Method - mohsen habibi; Alireza Ghadrdan; Ahmad Shahrabi Farahani (پژوهش نامه معارف قرآنی, 2022)
Since the literal (basic) meaning of the article "Ha Fa Za" (ح ف ظ) stands in opposition to the meaning of "N S I" (ن س ی), It is used in a position that due to commitment and a little neglect and complete loyalty of the mind in the process of storing concepts, an entity is not abandoned and as a result remains healthy and does not perish. Also, the difference between this root and other roots that are similar to the substance "Ha fa za" in terms of meaning is that this substance does not express the cause of non-destruction, that is, a special state in the process itself. It does not contain and the place of protection must be collectable and maintainable, finite and limitable. Also, in this material, time and its continuity are not considered. Therefore, considering the gradualness in the meaning of the verb "descending" in the ninth verse of Surah Hajar and the fact that "Al-Dhikr" has a gradual descent, because the word "Al-Hafizun", on the one hand, implies a place of finite and collected research and On the other hand, time and continuity are not considered in it, and there is no attention to time in it, it implies the meaning of proof and stability of protection. In other words, by only using the literal meaning of Hafez for protection, it does not move with the gradual movement of Mahfouz (Al-Dhikr) over time. It means that God protects the entire Holy Quran at all times.